2003
DOI: 10.1292/jvms.65.607
|View full text |Cite
|
Sign up to set email alerts
|

Development of Peyer's Patch and Cecal Tonsil in Gut-Associated Lymphoid Tissues in the Chicken Embryo

Abstract: ABSTRACT. It is well known that chicken B cells develop in the bursa of Fabricius (BF), which is categorized as gut-associated lymphoid tissue (GALT). Chicken GALT also includes Peyer's patch (PP) and cecal tonsil (CT). The relationship between these tissues in GALT during B cell development is currently unknown. In this study, we conducted comparative examination of PP, CT and BF developmen t during embryogenesis using immunohistochemical staining. On day 13 of embryogenesis (E13), accumulation of MHC class I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
1
15
1
2
Order By: Relevance
“…The functional development of the intestines as a digestive organ seems to be closely related to its development as a major lymphoid organ (Thompson et al, 1996). Previous studies showed that early feed intake has a positive effect on the development and maturation of the gut associated lymphoid tissue (GALT), which includes the cecal tonsils, bursa of Fabricius, Peyer's pathes and other lymphoid nodules, and provides both local and systemic protection in young chicks (Dibner et al, 1998;Friedman et al, 2003;Kajiwara et al, 2003). Delayed access to feed has shown to decrease bursa weight (Dibner et al, 1998) and to delay the development of T and B lymphocytes in the hindgut in the first 2 weeks of life (Bar-Shira et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The functional development of the intestines as a digestive organ seems to be closely related to its development as a major lymphoid organ (Thompson et al, 1996). Previous studies showed that early feed intake has a positive effect on the development and maturation of the gut associated lymphoid tissue (GALT), which includes the cecal tonsils, bursa of Fabricius, Peyer's pathes and other lymphoid nodules, and provides both local and systemic protection in young chicks (Dibner et al, 1998;Friedman et al, 2003;Kajiwara et al, 2003). Delayed access to feed has shown to decrease bursa weight (Dibner et al, 1998) and to delay the development of T and B lymphocytes in the hindgut in the first 2 weeks of life (Bar-Shira et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The development of the bursa and other GALT such as cecal tonsils and Peyer's patches starts during late embryogenesis (Kajiwara et al, 2003). At the time of hatching, the bursal duct opens and simultaneously, transport of environmental antigens into the bursal lumen and further into the lymphoid follicles begins.…”
Section: Early Feeding and Development Of The Gut Immune Systemmentioning
confidence: 99%
“…The development of PP and CT starts during late embryogenesis (ED13), at the same time as the follicle of the bursa. The appearance of surface IgM-positive cells in PP and CT is independent of the development of the follicle of the bursa [113]. Mature lymphocytes capable of secreting immunoglobulins are not detected in the chick until 6 days after hatching [39].…”
Section: Embryonic Structures and Their Role In Egg Defensementioning
confidence: 99%